Proving Motive In Premeditated Murder Cases - Aturkian Laia; Muhammad Mustofa; Kristiawanto Kristiawanto (Asian Journal of Social and Humanities, 2025)
The proof of motive in the crime of premeditated murder plays a crucial role but faces significant challenges due to the absence of a clearly defined motive within Article 340 of the Indonesian Criminal Code, leading to varying interpretations and inconsistent applications of the law. Some judges consider motive as a basis for sentencing, while others do not, resulting in legal uncertainty and concerns over fairness and uniformity in judicial decisions. This research aims to analyze the position of motive proof within the crime of premeditated murder and propose an ideal concept for its future application. Using a normative legal research method with statutory, conceptual, and case study approaches, the findings reveal that the absence of a clear directive regarding motive causes inconsistent judicial practices and undermines legal certainty. The study highlights the need to explicitly incorporate motive as an essential element of proof in Article 340 to enhance fairness and consistency in judicial decisions. It concludes that integrating motive into the legal framework of premeditated murder is critical to ensuring clarity for judicial interpretation, upholding justice, and strengthening the reliability of the legal system.